PENERAPAN KONSTRUKTIVIS SOSIAL ( SOCIAL CONSTRUCTIVIS APPROACHES ) PADA MATA PELAJARAN PAI DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS X IPS DI MA AL-IHSAN KALIKEJAMBON TEMBELANG JOMBANG - Ula, Navilatul (JoEMS (Journal of Education and Management Studies), 2021)
The problem of this research is the application of social constructivists to determine learning outcomes so that it can improve student achievement. This research is a quantitative research and type of field research with a population of 40 students consisting of 21 students of class X IPS 1 and 19 students of X IPS 2. Data collection methods in this study are observation, learning outcome tests, interviews, and documentation. This study uses the dependent sample t test to find student learning outcomes after treatment. Based on the results of the analysis of the dependent sample t test using the SPSS 21.00 for Windows program on the pre-test and post-test scores for class X IPS, which amounted to 40 students, it was found that the Sig (2-tailed) was 0,000. Because the Sig (2-tailed) value is less than 0.05 (0.000 <0.05), Ho is rejected and Ha is accepted, which means that there is a significant difference between the pre-test and post-test learning outcomes. So it can be said that the use of social constructivist methods in the subject of Aqidah Akhlak class X IPS 1 and X IPS 2 MA Al-Ihsan Kalikejambon Tembelang Jombang is better than conventional learning methods.